Palliative Nerve Block for Penile Calciphylaxis: A Case Report on Ultrasound-Guided Phenol Neurolysis. Issue 3 (March 2021) - Mach, Steven; Collie, Mark A.; Pesce, Michael B.
Abstract : A 78-year-old man with uncontrolled diabetes, heart failure, and hemodialysis-dependent end-stage renal disease presented with intractable penile pain secondary to calciphylaxis and necrosis of his glans penis. Given pain refractory to pharmacologic management and refusal of surgery, treatment entailed an ultrasound-guided dorsal penile nerve block with 5 mL of aqueous 4% phenol bilaterally. The patient reported immediate relief and died pain-free 3 months later. While phenol nerve blocks are increasingly uncommon due to local tissue toxicity, the precision of ultrasound leverages phenol's denaturing and axonal demyelinating properties to facilitate long-term targeted neurolysis to palliate chronic nonmalignant pain.